ANALISIS KONSUMSI KOMIK DIGITAL TERHADAP PERSEPSI PASANGAN IDEAL OLEH PENGGUNA MUSLIM - Husna, Azizah Nur; Khuluq, Arif Husnul (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Abstract: The digitalization of media has significantly transformed information consumption preferences among Muslim communities, including the rising trend of digital comic readership across diverse age groups and genders. Digital comics have evolved beyond mere entertainment platforms to become influential agents in shaping social and relational constructs among Muslim users. This study aims to examine the implications of digital comic consumption on the perception of ideal partners among Muslim readers. Employing a qualitative research design with a descriptive analytical approach, data were collected through observation and in-depth interviews with 42 Muslim informants who actively engage with digital comics. The findings reveal four primary motives underlying digital comic consumption: information seeking, personal identity formation, social integration and interaction, and entertainment. The dominant genres consumed by Muslim users include action, romance, slice of life, fantasy, and royalty-themed narratives. Character representations and portrayals of ideal relationships within digital comics have the potential to positively influence users’ perceptions of ideal partners, including the reinforcement of positive values and character traits, integration of Islamic principles into partner preferences, formulation of realistic criteria for ideal partners, encouragement of self-reflection and understanding, and enhancement of media literacy and critical attitudes. Conversely, this trend may also yield negative implications, such as the formation of unrealistic partner expectations, decreased personal productivity, diminished real-world socialization skills, and adverse effects on physical and psychological well-being. This study contributes to a deeper understanding of the role of digital media in shaping relational constructs and ideal partner values within Muslim communities. Keywords: Analysis, Digital comics, Perception, Muslim, Ideal partner.